Transcranial brain parenchymal sonography in neurodegenerative and psychiatric diseases - Mijajlovic, Milija D; Tsivgoulis, Georgios; Sternic, Nadezda (Journal of ultrasound in medicine, 2014)
Transcranial sonography is a highly sensitive noninvasive sonographic method for detection of early and specific echogenic changes in basal ganglia of patients with some neurodegenerative diseases. Transcranial sonography showed substantia nigra hyperechogenicity as a typical echo feature in idiopathic Parkinson disease and lenticular nucleus hyperechogenicity as a characteristic finding in atypical parkinsonian syndromes. Brain stem raphe hypoechogenicity or interruption has been shown to be highly prevalent in patients with unipolar depression as well as depression associated with certain neurodegenerative diseases. Transcranial sonography also revealed basal ganglia hyperechoic changes in movement disorders with trace metal accumulation such as Wilson disease, some entities of neurodegeneration with brain iron accumulation, as well as several forms of spinocerebellar ataxia. Transcranial sonography is a valuable neuro imaging method for early and differential diagnosis and follow-up of patients with neurodegenerative and psychiatric diseases.
Keywords: neurodegenerative diseases; vylepšení obrazu; ultrasound education; neurodegenerativní nemoci; Humans; lidé; Image Enhancement; ultrasonografie dopplerovská transkraniální; Neurodegenerative Diseases; psychiatric diseases; duševní poruchy; basal ganglia echogenicity; Ultrasonography, Doppler, Transcranial; transcranial sonography; Mental Disorders